Comparing patent protection in Indonesia with that in Singapore and Hong Kong - Lu Sudirman; Hari Sutra Disemadi (Legality : Jurnal Ilmiah Hukum, 2021)
The discovery of technology has a huge impact on the economy of a country, so many countries focus on developing technology and apply this technology in their respective countries. Technological inventions must register patent rights to obtain legal protection to avoid losses that will harm inventors, stimulate creativity in creating new technologies and create fair business competition among companies engaged in technology. This normative research aims to compare patent protection in Indonesia, Singapore, and Hong Kong. The benefit of this research is that it can contribute to scientific literature in the field of patent rights, can provide an overview of the form of patent rights arrangements in several countries outside Indonesia, so as to avoid disputes and/or misunderstandings with other countries. The participation of Indonesia, Singapore, and Hong Kong in ratifying the Convention on the World Trade Organization and the agreement on the Trade Aspects of Intellectual Property Rights (TRIPs) obliges these countries to establish regulations on patents in their respective countries. Although the application of patent law in Indonesia, Singapore, and Hong Kong is based on the terms of the TRIPs agreement, the implementation and regulations must have differences. Patent registration in Indonesia, Singapore, and Hong Kong have the same procedure, namely fulfilling the formal requirements, substantive examination, then the announcement stage. The term of patent protection in Indonesia and Singapore is similar, which is 20 years from the date of filing. However, it is different from Hong Kong, namely from the date of filing. In patent disputes, there are two ways of settlement, namely litigation and non-litigation. Patents in Indonesia, Singapore, and Hong Kong have another similarity, namely that they are transferable and can be licensed. The focus of this research is only to compare the application of patent law and not to examine its strengths and weaknesses, so it is considered important to do further research on this matter.